Enhancing supervised classifications with metamorphic relations - Xu, Liming; Towey, Dave; French, Andrew P.; Benford, Steve; Zhou, Zhi Quan; Chen, Tsong Yueh (2018)
We report on a novel use of metamorphic relations (MRs) in machine learning: instead of conducting metamorphic testing, we use MRs for the augmentation of the machine learning algorithms themselves. In particular, we report on how MRs can enable enhancements to an image classification problem of images containing hidden visual markers ("Artcodes").